The disposition effect in farmers' selling behavior: An experimental investigation - Elisabeth Vollmer; Daniel Hermann; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2017)
The identification of the optimal selling time of stored goods is among the most essential eco-nomic decisions on a farm. Beyond monetary aspects, behavioral factors may influence farmers' selling behavior. In financial economics, the disposition effect is a commonly observed phenomenon. It indicates that investors hold losing stocks too long, while they sell stocks that have increased in value too early. In the context of agriculture, this behavioral bias has not been analyzed thoroughly yet. To close this research gap, we conducted an incentivized online experiment with 112 farmers in Germany. The experimental design was based on well-proven experiments from financial economics and adapted to an agricultural decision context where stored goods must be sold. Farmers were provided information on the uncertain price developments. In addition, lotteries were conducted to elicit farmers' risk attitude, probability weighting, and loss aversion. Results indicate that there is a robust disposition effect in farmers' selling behavior. Furthermore, more loss-averse farmers exhibited a higher disposition effect.
Keywords: 330; disposition effect; experiments; farmers